Modified N–P Interpolation Theory for Closed Loop Pole Placement. Issue 5 (24th November 2014) - Aruna, B.; Devanathan, R.
Abstract Khargonekar and Tannenbaum have shown how to modify the Nevanlinna‐Pick (N–P) interpolation theory to design an internally stable and robust controller. In this paper, we present a new modification of the N‐P theory so that closed‐loop poles can be placed inside a circular region in the left half of the complex plane, in addition to the control system design being robust and internally stable. This ensures a minimum damping of the closed‐loop system. Numerical examples illustrate the theory.